Applying Video Flipped Classroom Model; to Enhance Students Speaking Achievement at Eleventh Grade - Sanusi, Irma Sri Wahyuni; Alimin, Alimin (Universitas Halu Oleo, 2021)
This study aims to find out whether Flipped Classroom Model enhances studentsâ€™ speaking skill or not. The research question formulated â€œIs there any significant effect by applying video flipped classroom model on studentsâ€™ speaking achievement.â€ This study applied quasi experimental design by using two classes, namely: experimental group and control group that given pre-test and post-test. The sample of this study is the eleventh grade students of SMAN 1 Raha who are registered in academic year 2019/2020. This study conducts from January, 14 to 4 February, 2020. The instrument used for collecting data is oral test and the data is analyzed by using descriptive statistic that is counting in SPSS 16.0. The findings show that the students speaking score in experimental score is higher than the students speaking score in control group. It is because the students who taught by applying flipped classroom model in hortatory exposition is easy to speak up in front of the classroom because they have enough knowledge of vocabulary, so it supports the students to memorize the context that they want to speak up. It is proved by the comparison of the mean score from control group and experimental group, where the mean score in control group is 2.45 and the mean score in experimental group is 2.79. Besides, the gain score from control group to experimental group are 0.34. Furthermore, the effect size is 0,27. It indicates that the effect size is categorized into large criteria. It means that there is any significant effect of teaching speaking by applying flipped classroom model in teaching speaking in the eleventh grade students of SMAN 1 Raha.